A fully integrated 43.2-Gb 4 demux IC in InP HBT technology. - Nielsen, S.
A 43.2-Gb/s clock and data recovery/demultiplexer (CDR/DMUX) integrated circuit (IC) implemented in InP heterojunction bipolar transistor (HBT) technology is demonstrated. The IC is fully integrated, requiring only a single external capacitor for complete functionality. The IC exceeds extrapolated SONET/SDH jitter tolerance specifications, operates with an industry-standard +3.3-V power supply, and dissipates 3.3 W.
Keywords: 3.3 V; 3.3 W; 43.2 Gbit/s.; HBT technology; PLL loop filter; SONET/SDH specifications; Clock and data recovery; Demultiplexer IC; Extrapolated jitter tolerance specifications; Fully integrated; Optical communication equipment; Optical receiver system; Phase detector; Ring oscillator topology; Single external capacitor